1991
DOI: 10.1002/ana.410300503
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral amyloid angiopathy without and with cerebral hemorrhages: A comparative histological study

Abstract: To identify those factors associated with cerebral hemorrhage among brains with cerebral amyloid angiopathy (CAA), we undertook a comparative postmortem histopathological study of amyloid-containing vessels in the brains of patients with and without hemorrhage. Those without hemorrhage were represented by the following two groups: (1) elderly patients from a large general hospital (n = 66; age range, 75-107 years) and (2) patients with various neuropsychiatric disorders (n = 70; age range, 27-96 years). CAA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
414
6
12

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(454 citation statements)
references
References 63 publications
22
414
6
12
Order By: Relevance
“…Cerebral amyloid angiopathy is characterized by the accumulation of A in the vessel wall of small cortical and leptomeningeal arteries and arterioles, and to a lesser extent in the wall of cortical capillaries. 15,16 The process of A accumulation in CAA is not fully understood. An earlier theory suggested that A in CAA directly originates from smooth muscle cells in the vessel wall.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral amyloid angiopathy is characterized by the accumulation of A in the vessel wall of small cortical and leptomeningeal arteries and arterioles, and to a lesser extent in the wall of cortical capillaries. 15,16 The process of A accumulation in CAA is not fully understood. An earlier theory suggested that A in CAA directly originates from smooth muscle cells in the vessel wall.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…Moderate CAA is often defined as circumferential staining of A in leptomeningeal and cortical blood vessels, while severe CAA is usually characterized by additional vascular pathologies such as concentric splitting of the vessel wall (double barreling) or appearance of A in the perivascular neuropil (dyshoric changes). 12,16,29 Moderate-to-severe CAA seems to be most strongly associated with clinical symptoms. 12 Cerebral amyloid angiopathy is not equally distributed throughout the brain, but predominantly affects vessels in posterior cortical brain regions, 8,30 whereas vessels in the brain stem and basal ganglia are relatively spared.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…Cerebral amyloid angiopathy (CAA) is found in approximately 90% of AD cases and consists of deposits of amyloid beta (Aβ) peptide in and around the perivascular spaces of vessels (Premkumar et al, 1996). This eventually leads to the death of smooth muscle cells and endothelial cells in the vicinity of amyloid deposits (Vonsattel et al, 1991). The presence of Aβ deposits in the vasculature can also lead to proinflammatory responses including microglia/macrophage activation (Giulian et al, 1995) and complement activation (McGeer et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…These amyloid deposits are similar to those seen in Alzheimer's disease. The amyloid-beta fragment is the primary component of the plaques [18,19].…”
Section: Cerebral Amyloid Angiopathymentioning
confidence: 99%